(untitled) - Rowe, William T. (Stanford, Calif., 2001)
In this magisterial study, the author draws on Chen’s life and career to answer a range of questions: What did mid-Qing bureaucrats think they were doing? How did they conceive the universe and their society, what did they see as their potential to “save the world,” and what would the world, properly saved, be like? The answers to these questions are important not only because vast numbers of people were subject to these officials’ governance, but because the verdict of their successors was that they did their jobs remarkably well and should be emulated.
Keywords: Chính trị và nhà nước; Trung Quốc; Thế kỷ 18